Bacillus thuringiensis (serotype 14) crystal toxins shows non-toxic effects on fingerlings freshwater fish cyprinus carpio against the mosquito larvae. - DR. SHIVARAJ YALLAPPA (International Journal of Pharma and Bio Sciences, 2019)
In the present day situations, human being suffer a lot due to the unadoptable policies of Pesticides companies that produce different bacteria strains Pesticides companies and which produced different bacteria strains like Bacillus thuringiensis. (Serotype 14) Crystal toxins is a gram positive, rod shaped and aerobic soil bacteria. B. thuringiensis is a bacterium that is not toxic to terrestrial and aquatic living organisms and other mammals but is toxic to certain insects when ingested. B. thuringiensis works as an insecticide by producing a crystal-shaped protein (Cry toxin) that specifically kills certain insects. These bacteria produces a proteinaceous parasporal crystal in the sporangium at the time of sporulation. These proteins possess insecticidal properties and are called Bt-toxins or delta endotoxins and also called as Insecticidal Crystal Proteins (ICPs). It is not a single toxin but a class of toxic proteins produced from protoxin that are degraded by proteolytic enzyme to form smaller toxic peptides. In this study, the mosquito larvae are considered as first predators which feed on some protozoans and bacteria, and fingerlings freshwater fishes are considered as the secondary predators which feed on B. thuringiensis induced mosquito larvae. The fixation of concentration levels to larva was 9 gm of (Serotype 14) Bacillus thuringiensis induced to 10 liter of water which contains 100 mosquito larvae and 10 fishes were consumed by the entire larva and the exposure periods were Day-1 to Day-30 and Recovery Period will be 15 days since during these days there is no toxicity of B. thuringiensis on fishes were conformed. When these larvae feed on Bacteria, B. thuringiensis show behavioral changes like erratic swimming, slow motility and the larvae move towards the surface of water and regurgitation and sudden mortality were observed because of Bt-crystals effects on enzyme present in the larvae i.e. cytochrome-c-oxidases due to oxidative stress and the liberated crystal toxin like Cry-II and Cry-IV bind into the larva gut cell membrane it shows the paralyzes the digestive tract and forming a pore in that regions and results in the death of the mosquito larvae. The current study shows that B. thuringiensis bacteria produces toxins in nature and it shows the effect against the mosquito larvae but (Serotype 14) Crystal toxins shows non-toxic effects on fingerlings freshwater fish Cyprinus carpio.